Butyrate Drives Metabolic Rewiring and Epigenetic Reprogramming in Human Colon Cancer Cells. Issue 12 (28th April 2022) - Wang, Lujing; Shannar, Ahmad Abdel Fat; Wu, Renyi; Chou, Pochung; Sarwar, Md Shahid; Kuo, Hsiao‐chen; Peter, Rebecca Mary; Wang, Yujue; Su, Xiaoyang; Kong, Ah‐Ng
Abstract : Scope: Butyrate (B) is a short‐chain fatty acid produced by dietary fiber, known to inhibit histone deacetylases (HDACs) and possess cancer‐preventive/anticancer effects. However, the role of B in metabolic rewiring, epigenomic reprogramming, transcriptomic network, NRF2 signaling, and eliciting cancer‐preventive effects in colorectal cancer (CRC) HCT116 cell remains unclear. Methods and results: Sodium butyrate (NaB) dose‐dependently inhibits the growth of CRC HCT116 cells. NaB inhibits NRF2 / NRF2 ‐target genes and blocks NRF2 ‐ARE signaling. NaB increases NRF2 negative regulator KEAP1 expression through inhibiting its promoter methylation. Associative analysis of DEGs (differentially expressed genes) from RNA‐seq and DMRs (differentially methylated regions) from CpG methyl‐seq identified the tumor suppressor gene ABCA1 and tumor promote gene EGR3 are correlated with their promoters' CpG methylation indicating NaB regulates cancer markers through modulating their promoter methylation. NaB activated the mitochondrial tricarboxylic acid (TCA) cycle while inhibited the methionine metabolism which are both tightly coupled to the epigenetic machinery. NaB regulates the epigenetic enzymes/genes including DNMT1, HAT1, KDM1A, KDM1B, and TET1 . Altogether, B's regulation of metabolites coupled to the epigenetic enzymes illustrates the potential underlying biological connectivity between metabolomics and epigenomics. Conclusion: B regulates KEAP1 / NRF2 signaling, drives metabolic rewiring, CpG methylomic, and transcriptomic reprogramming contributing to the overall cancer‐prevention/anticancer effect in the CRC cell model. Abstract : Integration of CpG Methyl‐seq, RNA‐seq, and LC/MS technologies to dissect the connectivity mechanism of CpG methylation, mRNA transcriptomic, and metabolic rewiring in human colorectal cancer cells after sodium butyrate (NaB) treatment. NaB regulates the epigenomic via rewiring metabolomics and regulating epigenetic genes, consequently, modulates the tumor promote/suppress genes and Kelch‐like‐ECH‐associated protein1/nuclear factor erythroid‐2‐like2 ( KEAP1 / NRF2) signaling to exhibit anti‐cancer effects.